The Effects of Dapagliflozin in Patients With Heart Failure Complicated With Type 2 Diabetes: A Meta-Analysis of Placebo-Controlled Randomized Trials - Zhai, Miaobo; Du, Xin; Liu, Changmei; Xu, Huipu (Frontiers in Clinical Diabetes and Healthcare, 2021)
Background Cardiovascular disease threatens the health and quality of life of individuals, particularly those with type II diabetes. Recently, some studies have reported the effect of sodium-glucose cotransporter 2 (SGLT2) inhibitors in reducing the rates of hospitalization or urgent visits, resulting in IV therapy for heart failure in patients with type 2 diabetes mellitus (T2DM). Methods We did a comprehensive search in electronic databases from inception through July 2020 for randomized-controlled trials, using the keywords “sodium-glucose cotransporter-2 inhibitor”, “dapagliflozin”, “heart failure”, “cardiovascular outcomes”, “major adverse cardiovascular events”, “all-cause mortality”, and “cardiovascular death”. Random-effects summary odds ratios (OR) were constructed using M-L heterogeneity model. Results Five trials with 5,252 patients were ultimately included. The incidence of hospitalization for heart failure (HHF) (n=4, OR=0.74; 95% CI, 0.61 to 0.88; I2 = 0%) and all-cause mortality (ACM, n=4, OR=0.76; 95% CI, 0.66 to 0.94; I2 = 0%); was reduced by dapagliflozin, respectively, in all heart failure patients, without obvious heterogeneity. The incidence of cardiovascular death in dapagliflozin was lower than that in placebo without statistically significant (CVD, n=5, OR=0.84; 95% CI, 0.69 to 1.03; I2 = 0%). In HFrEF subgroup, dapagliflozin was associated with a reduced incidence of hospitalization for heart failure (n=4, OR=0.74; 95% CI, 0.60 to 0.91; I2 = 0%), cardiovascular death (n=4, OR=0.72; 95% CI, 0.58 to 0.91; I2 = 8%), and all-cause mortality (n=3, OR=0.70; 95% CI, 0.50 to 0.99; I2 = 43%) without significant heterogeneity. In contrast, in the HFpEF subgroup, there was no difference in the incidence of cardiovascular death (n=2, OR=1.45; 95% CI, 0.95 to 2.22; I2 = 0%) and all-cause mortality (n=2, OR=1.04; 95% CI, 0.76 to 1.43; I2 = 0%) between dapagliflozin and placebo. Conclusion In our study, dapagliflozin performed a statistical reduction in the rate of heart failure hospitalization, cardiovascular death, and all-cause mortality in patients with HFrEF and diabetes. However, in the HFpEF subgroup, dapagliflozin did not show a significant cardiovascular protective effect.